2014
DOI: 10.1590/s1413-78522014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of sensory anastomoses in the hand

Abstract: Objective: The aim of this study is to evaluate the prevalence, topography and morphometry of sensitive nervous anastomoses in the hand. Methods: Thirty anatomic parts irrespective of race, gender and age have been dissected. Measurements of anastomoses' length, origin and terminus regarding the transverse carpal ligament were noted. The anastomoses were classified according to the scheme proposed by Meals & Shaner and modified by Bas & Kleinert. Results: Type 1 anastomosis was the most prevalent. The distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…For RCA, 4 studies reporting data were cadaver, and 2 were electrophysiological . A total of 10 studies concerning BA were cadaver, and only 1 was electrophysiological…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For RCA, 4 studies reporting data were cadaver, and 2 were electrophysiological . A total of 10 studies concerning BA were cadaver, and only 1 was electrophysiological…”
Section: Resultsmentioning
confidence: 99%
“…Data on types of BA were reported in 10 studies ( n = 486 hands) . The analysis found that the most frequent type of BA was type 1, with a pooled prevalence of 86.2% (95% CI, 77.3%–91.6%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations